ATG12 is involved in the antiviral immune response in large yellow croaker (Larimichthys crocea). Issue 119 (December 2021) - Wei, Zuyun; Wen, Qiao; Li, Wanru; Yuan, Xiaoqin; Fu, Qiuling; Cui, Zhengwei; Chen, Xinhua
Abstract: ATG12, a core autophagy protein, forms a conjugate with ATG5 to promote the formation of autophagosome membrane, and plays an important role in antiviral immunity. However, little is known about the function of ATG12 in fish. Here, we cloned the open reading frame (ORF) of large yellow croaker ( Larimichthys crocea ) ATG12 ( Lc ATG12), which is 354 nucleotides long and encodes a protein of 117 amino acids. The deduced Lc ATG12 possesses a conserved APG12 domain (residues 31 to 117), and shares 91.45% identities with ATG12 in orange-spotted grouper ( Epinephelus coioides ). Lc ATG12 was constitutively expressed in all examined tissues, with the highest level in intestine. Its transcript was also detected in primary head kidney granulocytes (PKG), primary head kidney macrophages (PKM), primary head kidney lymphocytes (PKL), and large yellow croaker head kidney (LYCK) cell line, and was significantly up-regulated by poly(I:C). Lc ATG12 was regularly distributed in both cytoplasm and nucleus of LYCK and epithelioma papulosum cyprinid (EPC) cells. Overexpression of Lc ATG12 in EPC cells significantly inhibited the replication of spring viremia of carp virus (SVCV). Further studies reveled that Lc ATG12 could induce the occurrence of autophagy in LYCK cells. Furthermore, overexpression of Lc ATG12 in LYCK cells increased the expression levels of large yellow croaker type I interferons (IFNs, IFNc, IFNd, and IFNh), IFN regulatory factors (IRF3 and IRF7), and IFN-stimulated genes (PKR, Mx, and Viperin). All these data indicated that Lc ATG12 plays a role in the antiviral immunity possibly by inducing both autophagy and type I IFN response in large yellow croaker. Highlights: Lc ATG12 was constitutively expressed in tissues and immune cells, and upregulated in immune cells by poly(I:C). Lc ATG12 was evenly distributed in the cytoplasm and nucleus of LYCK and EPC cells. Overexpression of Lc ATG12 inhibited SVCV replication in EPC cells. Lc ATG12 induces both autophagy and type I IFN response to perform its antiviral function.